PERBEDAAN HASIL BELAJAR KOGNITIF FISIKA DENGAN STRATEGI TIPE PREDICTION GUIDE PADA PENDEKATAN INDUKTIF DAN DEDUKTIF PADA POKOK BAHASAN GETARAN DAN GELOMBANG KELAS VIII SMP N 5 DEPOK - Warsito Warsito (UIN Sunan Gunung Djati Bandung, 2018)
This study aims to determine differences in cognitive physics learning outcomes with Prediction Guide type strategies on deductive and inductive approaches in SMP N 5 Depok. This type of research is a quasi-experimental study using a pretest-posttest experimental design. The sample in this study was determined by random cluster sampling technique. The population of this study was all students of class VIII of SMP Negeri 5 Depok, and the sample was 36 students from class VIII A as an experimental class given teaching with a deductive approach and 36 students from class VIII B as a control class given teaching with an inductive approach. The hypothesis testing method used is independent sample t-test. The results of this study indicate that there is no significant difference in the improvement of students' cognitive learning outcomes between the experimental class and the control class.